Miles to Go - Cyrus, Miley and Liftin, Hilary (Bath Parragon, 2009)
For the first time ever, read Miley Cyrus' story in this, her only official autobiography. It is a unique look inside the life of an international megastar, including never-before-seen photographs, poems, drawings and stories!
Include Illustration
Keywords: Singers -- United States -- Television actors and actresses